“Hands Off Our National Parks”: The Alpine Club of Canada Hydro-development Controversies in the Canadian Rockies, 1922-1930 - Reichwein, PearlAnn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1995)
AbstractThrough the 1920s, hydro development proposals for irrigation and power dams impinged on Canada's national parks in the Rockies. The Alpine Club of Canada — a mountaineering organization formed in 1906 — rallied opposition to dams and insisted that national parks were an inviolable public domain. National Parks Commissioner J.B. Harkin and ACC Director A.O. Wheeler created an alliance that highlighted the club's role as a key interest group and recreational stakeholder with a shared vision of the mountain parks. Conflicts over dams in Rocky Mountains and Waterton Lakes national parks were politically and philosophically compared to the great battle of the “Hetch Hetchy” aqueduct in California.